The Relationship Between Behavior Of Type II Diabetes Mellitus Patients With Diet Therapy Compliance In Medan Selayang Area Year 2020 - Nurliaty Nurliaty; Reny Juliana Sihombing (Jurnal EduHealth, 2021)
Diabetes Mellitus is a metabolic disorder caused by a lack of the hormone insulin to process carbohydrate metabolism normally, adherence is the level of patient carrying out the method of treatment and behavior recommended by a doctor or by others. Insulin has a major role in regulating glucose levels in the blood, namely entering glucose into cells. This study aims to analyze the relationship between the behavior of type II diabetes mellitus sufferers and adherence to dietary therapy in Medan Selayang District in 2020 which was carried out from May to August 2020, with a correlation description design using the total sampling technique of 58 type II DM sufferers who participated in this study. . Data collection using a questionnaire sheet. Data analysis was performed using univariate analysis and then using Spearman's correlation test to see a significant relationship between the behavior of type II DM patients and adherence to diet therapy. The results of the study showed that there was a significant relationship between the behavior level of type II DM sufferers and adherence to diet therapy (Sig. (2-tailed) = 0.03, r = 0.59) where out of 58 people (75.9%) had type II Diabetes Mellitus In moderate behavior there were 33 people (56.9%) who did not comply with diet therapy and 11 people (19.0%) adhered to diet therapy. So it can be concluded that there is a significant relationship between the behavior of type II DM sufferers and adherence to diet therapy in Medan Selayang District in 2020.